Effectiveness of High‐Intensity Interval Training for Fitness and Mobility Post Stroke: A Systematic Review. Issue 8 (30th May 2019) - Wiener, Joshua; McIntyre, Amanda; Janssen, Scott; Chow, Jeffrey TY; Batey, Cristina; Teasell, Robert
Abstract : Objective: To evaluate the evidence on the effectiveness of high‐intensity interval training (HIIT) in improving fitness and mobility post stroke. Type: Systematic review. Literature Survey: Medline, Embase, CINAHL, PsycINFO, and Scopus were searched for articles published in English up to January 2018. Methodology: Studies were included if the sample was adult human participants with stroke, the sample size was ≥3, and participants received >1 session of HIIT. Study and participant characteristics, treatment protocols, and results were extracted. Synthesis: Six studies with a total of 140 participants met inclusion criteria: three randomized controlled trials and three pre‐post studies. HIIT protocols ranged 20 to 30 minutes per session, 2 to 5 times per week, and 2 to 8 weeks in total. HIIT was delivered on a treadmill in five studies and a stationary bicycle in one study. Regarding fitness measures, HIIT produced significant improvements in peak oxygen consumption compared to baseline, but the effect was not significant compared to moderate intensity continuous exercise (MICE). Regarding mobility measures, HIIT produced significant improvements on the 10‐Meter Walk Test (10MWT), 6‐Minute Walk Test (6MWT), Berg Balance Scale (BBS), Functional Ambulation Categories (FAC), Timed Up and Go Test, and Rivermead Motor Assessment compared to baseline. The effect of HIIT was significant compared to MICE on the 10MWT and FAC but not on the 6MWT or BBS. Conclusions: There is preliminary evidence that HIIT may be an effective rehabilitation intervention for improving some aspects of cardiorespiratory fitness and mobility post stroke. Level of Evidence: I.